First report of Strongylidae nematode from pilot whale (Globicephala macrorhynchus) by molecular analysis reveals the cosmopolitan distribution of the taxon - Junsiri, Witchuta; Islam, Sk Injamamul; Thiptara, Auyarat; Jeenpun, Autthaporn; Sangkhapaitoon, Piyanan; Thongcham, Khunanont; Phakphien, Rattanakorn; Taweethavonsawat, Piyanan (Frontiers in Veterinary Science, 2023)
This study investigates the identification, genetic composition, and placement in the evolutionary tree of a particular nematode species found in a short-finned pilot whale in the Gulf of Thailand. To accomplish this, we utilized various methods, including microscopic observations, molecular techniques, and comparative analyses to better understand the characteristics of this parasite. Initially, we concentrated on studying the 18s rDNA sequence through nested PCR, resulting in a 774-bp product. After conducting a BLASTn analysis, we discovered that there were only a few sequences in the GeneBank that shared similarities with our nematode, particularly with Cyathostomum catinatum, although the percent identity was relatively low. To confirm the uniqueness of our sequence, we constructed a phylogenetic tree that demonstrated a distinct branch for our nematode, suggesting significant genetic differentiation from C. catinatum. Additionally, we sequenced a 399-bp section of the ITS2 gene using PCR, and the resulting data showed a close association with the Strongylidae family, specifically with Cylicocyclus insigne. This was further confirmed by BLASTn and CD-HIT-est results, which indicated a 99 and ~94% sequence homology with C. insigne, respectively. The ITS2 phylogenetic tree also supported the position of our isolated sequence within the Strongylidae family, clustering closely with C.insigne. Our findings shed light on the genetic connections, taxonomy, and evolutionary trends within the Strongylidae family, with a particular focus on the widespread nature of the Cylicocyclus genus. This study emphasizes the importance of utilizing molecular techniques and interdisciplinary approaches to gain insight into nematode diversity, evolution, and ecological dynamics in marine environments.